The Contribution of a Geophysical Data Service: The International Service of Geomagnetic Indices - M Menvielle (Data Science Journal, 2013)
Geomagnetic indices are basic data in Solar-Terrestrial physics and in operational Space Weather activities. The International Service of Geomagnetic Indices (ISGI) is in charge of the derivation and dissemination of the geomagnetic indices that are acknowledged by the International Association of Geomagnetism and Aeronomy (IAGA, an IUGG association). Institutes that are not part of ISGI started early in the Internet age to circulate on-line preliminary values of geomagnetic indices. In the absence of quality stamping, this resulted in a very confusing situation. The ISGI label was found to be the simplest and the safest way to insure quality stamping of circulated geomagnetic indices.